2015
DOI: 10.1111/vec.12327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of premedication and other factors on the occurrence of acute transfusion reactions in dogs

Abstract: While most TRs were mild, there were some serious reactions observed including hemolysis, dyspnea, and 6 deaths. Immune-mediated disease was associated with development of a TR, while transfusion during the perioperative period was associated with lower likelihood of reaction. Packed RBC transfusions were associated with development of acute TRs. Overall occurrence of TR was not significantly altered with premedication; however, when evaluated alone, antihistamines decreased the incidence of acute allergic rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(99 citation statements)
references
References 43 publications
(249 reference statements)
5
92
1
1
Order By: Relevance
“…A study in dogs reported a transfusion reaction rate of 15%, with reactions being more common with pRBC transfusions compared to other blood products (Bruce et al . ). In people, transfusion reactions are well defined and rates of between 0.2 and 3.8% have been reported, with variation between studies and blood products administered (Kato et al .…”
Section: Discussionmentioning
confidence: 97%
“…A study in dogs reported a transfusion reaction rate of 15%, with reactions being more common with pRBC transfusions compared to other blood products (Bruce et al . ). In people, transfusion reactions are well defined and rates of between 0.2 and 3.8% have been reported, with variation between studies and blood products administered (Kato et al .…”
Section: Discussionmentioning
confidence: 97%
“…None of the 7 dogs with acute reactions in that study 20 had a prior transfusion, so crossmatching was not performed before administration of RBCs. In another study, 21 all dogs that had a hemolytic transfusion reaction (4/558 [0.7%]) were transfusion-naïve dogs that did not have a crossmatch evaluation before the transfusion was administered. Because our study was retrospective and some medical records were incomplete, the incidence of transfusion reactions in the present study could not be properly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…11 Additionally, a recent study in dogs that included 412 FFP transfu-sions reported an ATR rate of 8%, which was lower than packed RBCs (pRBCs) (17%) and whole blood (15%). 18 Red cell rates of ATR in cats are reported to be between 2.2% and 8.7% and, more recently, up to 17% and 29%, 13,[19][20][21][22] whereas the rate of FFP ATR remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that coagulopathy would be the most common indication for FFP transfusion, and the rate of ATR would be comparable to studies in dogs. 11,12,18 It was also hypothesized that FFP administration would result in improvements in blood pressure, total plasma protein, and prothrombin time (PT)/aPTT. Finally, we hypothesized that the transfusion dose administered (in mL/kg) would be lower in cats as compared to people and dogs.…”
Section: Introductionmentioning
confidence: 99%